PENDIDIKAN DEMOKRASI - Ade Wahyudi; Ade Tegar; Arifandi; Budi Pratama; Reza Raihanda; Musdanil; Rizky wanda; Rizky maulana; Satria; Tirta; Yogi; Zikri; Zulkarnain (CV. Multi Kreasi Media, 2022)
Democracy comes from the Greek words